Asia-Pacific coasts and their management : states of environment - Mimura, Nobuo, 1949- (Coastal systems and continental margins ;, 2008)
"This book gives an overview of the understanding of the drivers, state, and responses to coastal environmental changes in the Asia-Pacific region. It provides perspectives on current and anticipated environmental changes in the region's coastal areas to researchers, students, policy makers, coastal managers and other stakeholders." "This book will be of interest to researchers, undergraduate and graduate students in coastal science, engineering and management, to policy makers, coastal managers and coastal developers, and to the fishing industry."--Jacket